2018
DOI: 10.1002/ejoc.201701785
|View full text |Cite
|
Sign up to set email alerts
|

1,4‐Dithiane‐2,5‐diol: An Attractive Platform for the Synthesis of Sulfur‐Containing Functionalized Heterocycles

Abstract: This microreview highlights the utility of 1,4‐dithiane‐2,5‐diol (1) as a source for the in situ generation of 2‐mercaptoacetaldehyde (2), a versatile two‐carbon synthon featuring both electrophilic and nucleophilic reaction centres and widely utilized as an attractive platform for the preparation of sulfur‐containing molecules. We discuss the chemistry involved, mainly focusing on its applications to the construction of sulfur‐containing heterocyclic compounds including the thiophene and 1,3‐thiazole families… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 107 publications
0
15
0
Order By: Relevance
“…In a series of our publications, we demonstrated that the [3 + 2]-cycloaddition of in situ-generated thiocarbonyl S-methanides with activated electron-deficient ethenes is the method of choice for the preparation of differently substituted tetrahydrothiophenes (Huisgen et al, 1984;Mlostoń & Heimgartner, 2000). Recently, alternative methods have been published in a series of reports demonstrating the ongoing interest in their synthesis (Zamberlan et al, 2018). For example, Lewis acid-catalysed reactions of thiocarbonyl compounds with 'donor-acceptor cyclopropanes' have been reported (Augustin et al, 2017;Matsumoto et al, 2018).…”
Section: Chemical Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…In a series of our publications, we demonstrated that the [3 + 2]-cycloaddition of in situ-generated thiocarbonyl S-methanides with activated electron-deficient ethenes is the method of choice for the preparation of differently substituted tetrahydrothiophenes (Huisgen et al, 1984;Mlostoń & Heimgartner, 2000). Recently, alternative methods have been published in a series of reports demonstrating the ongoing interest in their synthesis (Zamberlan et al, 2018). For example, Lewis acid-catalysed reactions of thiocarbonyl compounds with 'donor-acceptor cyclopropanes' have been reported (Augustin et al, 2017;Matsumoto et al, 2018).…”
Section: Chemical Contextmentioning
confidence: 99%
“…The CSD contains crystal structure data with atomic coordinates for 3225 monomeric organic compounds with the string thiophene in the compound name, of which 70 are named as tetrahydrothiophenes and 32 contain no substituents on the ring S atom. Recently published monocyclic crystal structures of tetrahydrothiophenes include those of Duan et al 2017, Ram et al (2016), Zamberlan et al (2018) and Zhang et al (2018). Spirocyclic examples involving two cojoined fivemembered rings have been reported by Meninno et al (2017) and Wang et al (2018).…”
Section: Database Surveymentioning
confidence: 99%
“…The importance of such a structural motif is demonstrated by a variety of synthetic approaches to the formation of the tetrahydrothiophene ring. Among them, an application of the dithiane diol as a source of low‐weight building block covering nucleophilic and electrophilic functionalities deserves particular attention [2] . Decomposition of the stable dimer of mercaptoacetaldehyde by a base or heating was the pillar of the elaborated cascade Sulfa‐Michael/aldol reaction or aldol condensation resulting in the formation of the multi‐decorated tetrahydrothiophenes in a highly stereoselective fashion [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Among them, an application of the dithiane diol as a source of low-weight building block covering nucleophilic and electrophilic functionalities deserves particular attention. [2] Decomposition of the stable dimer of mercaptoacetaldehyde by a base or heating was the pillar of the elaborated cascade Sulfa-Michael/ aldol reaction or aldol condensation resulting in the formation of the multi-decorated tetrahydrothiophenes in a highly stereoselective fashion. [3] The majority of transformations involve an initial addition to simple Michael acceptors.…”
Section: Introductionmentioning
confidence: 99%
“…An ester obtained from dihydric alcohol such as 1,4-dithiane-2,5-diol and poly basic aliphatic carboxylic acid is used as plasticizer in cyanoacrylate adhesive [13]. It is reported that 1,4-dithiane-2,5-diol is the main source to synthesize sulphur containing heterocyclic compounds like thiophene and 1,3-thiazole families that have broad application in medicinal chemistry [14,15]. The 2-aminothiophene derivatives have interesting properties like antiviral and antitumour activites [16][17][18], GluR6 Antagonism [19], inhibition of p53-Mdm2 interaction [20].…”
Section: Introductionmentioning
confidence: 99%